ANALISIS KINERJA JARINGAN INTERNET FT-UNIMED DENGAN PROTOCOL ROUTING OPEN SHOTEST PATH FIRST (OSPF) DAN BORDER GATEWAY PROTOCOL (BGP) - Muhammad Dominique Mendoza; Eka Daryanto; Olnes Yosefa Hutajulu (Universitas Negeri Medan, 2022)
The use of the internet network during the Corona Virus pandemic known as COVID-19 increased rapidly because learning had to be done online, one of which was experienced at Fakultas Teknik, Universitas Negeri Medan. Some network disturbances often occur because of the large data transmission requests from the data center. This problem occurs because the network being used is still using a static routing protocol where the data path configuration must be updated manually by the operator. The solution to this problem is proposed to change the routing protocol from static routing to dynamic routing. The proposed dynamic routing protocols are open shortest path first (OSPF) and border gateway protocol (BGP). The choice of these two types of protocols is because they have better performance and can be implemented on any type of hardware. In this article, we will discuss the analysis of the implementation of the OSPF and BGP protocols with simulations carried out using packet tracer software. The results obtained from the simulation are analyzed and it is known that the OSPF protocol has better performance than the previous protocol, namely static routing and BGP protocol. Based on the criteria of throughput, packet loss, delay and jitter, it is known that the OSPF protocol has better performance on throughput, delay and jitter.Keywords : Static routing, dynamic routing, OSPF, BGP